Developing the Students’ Speaking Performance through Information Transfer Technique - Fitri Radhiyani (Jurnal Ad'ministrare, 2018)
The objective of this research are: (1) to describe whether the use of Information transfer technique developed the students’ speaking performance in terms of accuracy and fluency, (2) to describe the feedback of students’ attitude toward Information transfer technique. The researcher design was pre-experimental design, the sample consisted of 26 students of sixth semester of English Education study program, Faculty of Language and Literature, State University of Makassar, in 2007/2008 academic year, class A. the researcher data were collected by using two kinds of instruments; Speaking test for students’ achievement by using Information transfer technique and questionnaire for students’ attitude toward information transfer technique. Data on the students’ speaking performance in terms of accuracy and fluency were analyzed using t-test at 0.05 level of significance and the main score formula, and data on students’ attitude were analyzed using Likert scale. The result of the research are : (1) The use of Information transfer technique developed the students’ speaking accuracy in terms of acceptable pronunciation, correct grammar, and appropriate word choice, (2) The use of information transfer technique also developed the students’ speaking fluency, and (3) the students had very positive attitude toward the use of information transfer technique. Thus means that the use of information transfer technique is effective to be implemented in developing students’ speaking performance in terms of accuracy and fluency.